2022
DOI: 10.3390/life12081197
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Our Microbiota: Stimulation of the Immune/Semiochemical System and the Potential Amelioration of Non-Communicable Diseases

Abstract: Non-communicable diseases are those conditions to which causative infectious agents cannot readily be assigned. It is increasingly likely that at least some of these conditions are due to the breakdown of the previously mutualistic intestinal microbiota under the influence of a polluted, biocide-rich, environment. Following the mid-20th century African studies of Denis Burkitt, the environmental cause of conditions such as obesity has been ascribed to the absence of sufficient fibre in the modern diet, however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 143 publications
(187 reference statements)
0
5
0
Order By: Relevance
“…'All diseases begin in the gut'; this principle made by Hippocrates affected all aspects of therapeutic and research strategies in modern medicine. 25 Gut microbiota consists of about 100 trillion microorganisms weighing up to 1.5 kg; due to the numerous vital functions of these microbes, researchers consider them as a virtual organ. 26 Dysbiosis status, an imbalance in the composition of the gut microbiota, has been related to various diseases, especially autoimmune disorders.…”
Section: Discussionmentioning
confidence: 99%
“…'All diseases begin in the gut'; this principle made by Hippocrates affected all aspects of therapeutic and research strategies in modern medicine. 25 Gut microbiota consists of about 100 trillion microorganisms weighing up to 1.5 kg; due to the numerous vital functions of these microbes, researchers consider them as a virtual organ. 26 Dysbiosis status, an imbalance in the composition of the gut microbiota, has been related to various diseases, especially autoimmune disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, these microbes have a great deal of dependability when it comes to delaying the beginning of certain illnesses [16,17]. As a result, taking probiotics might offer more affordable options for managing illnesses [18][19][20][21].…”
Section: Figure 1 Influence Of Bifidobacteria On Promoting a Healthy ...mentioning
confidence: 99%
“…In the intestinal microbiota of the group that received high plant‐based protein, it was observed that bacterial species of the genus saccharolytic Prevotella , Roseburia , Eubacterium rectale , Faecalibacterium prausnitzii increased (David et al., 2014). Since different bacteria ferment each food component, an increase in bacterial colonisation using that food type occurs, and the dominant bacterial species can be shaped according to the diet (Smith et al., 2022). Dietary changes in the microbiota, depending on the type and duration of nutrition applied, it may have positive or negative effects on host health.…”
Section: Nutrient Role In Microbiotamentioning
confidence: 99%
“…Different approaches will be chosen for the patients with a markedly dysbiotic profile (determined as low diversity and an abundance of unfavourable or pathogenic microbiota leading to impaired functional status), moderately dysbiotic profile (defined as intermediate diversity and consisting of some favourable microorganisms with relatively preserved functional status), and favourable profile (Park et al., 2022). All these strategies mentioned above will provide a more optimised personalised cancer treatment and improved health (Smith & Jheeta, 2020; Smith et al., 2022).…”
Section: New Strategies Targeting the Microbiotamentioning
confidence: 99%